Integrasi Psikologi dan Spiritualitas Islam dalam Pendekatan Holistik Pemulihan Trauma - Syifa, Syifa; Nurjannah, Nurjannah (Sahabat Akademia Group, 2024)
Trauma is a psychological condition that deeply affects emotions, thoughts, and behavior. This study examines RF, a 15-year-old teenager, who experienced trauma due to family conflict and bullying. The research aims to explore RF's trauma, its effects on daily life, and recovery strategies using a holistic approach integrating modern psychology and Islamic spirituality. The study employs a qualitative descriptive method with data collected through interviews, observation, and documentation. Thematic analysis was used to identify key patterns related to RF's trauma. RF's trauma resulted from family conflict and verbal bullying, leading to low self-esteem, social withdrawal, and unresolved emotional distress. A holistic intervention combining psychological therapies like Gestalt and CBT with spiritual practices such as dhikr and Qur'an recitation significantly improved RF’s emotional balance. This integration addressed both emotional and spiritual needs, promoting recovery. The study demonstrates that a holistic approach combining psychology and spirituality offers better outcomes than conventional therapy. This innovative model addresses psychological, spiritual, and social dimensions, making trauma recovery a pathway for personal growth. Future research can explore its application across diverse populations and integrate digital tools to enhance accessibility and impact. The findings underline the need for a balanced approach that supports both emotional healing and spiritual resilience, offering practical insights for similar interventions.